THE MECHANISM, RATES AND CONSEQUENCES OF BASALTIC GLASS DISSOLUTION: I. AN EXPERIMENTAL STUDY OF THE DISSOLUTION RATES OF BASALTIC GLASS AS A FUNCTION OF AQUEOUS AL, SI AND OXALIC ACID CONCENTRATION AT 25°C AND PH = 3 AND 11 - Oelkers E.H.; Gislason S.R. (My University, 2001)
Steady state basaltic glass dissolution rates were measured as a function of aqueous aluminum, silica, and oxalic acid concentration at 25° C and pH 3 and 11. All rates were measured in mixed flow reactors, performed in solutions that were strongly undersaturated with respect to hydrous basaltic glass, and exhibited stoichiometric Si versus Al release. Rates are independent of aqueous silica activity, but decrease with increasing aqueous aluminum activity at both acidic and basic conditions. Increasing oxalic acid concentration increased basaltic glass dissolution rates at pH 3, but had little affect at pH 11. All measured rates can be described within experimental uncertainty using r=k aH+3aAl+3 0.35r signifies the surface area normalized basaltic glass steady state dissolution rate, k refers to a rate constant equal to 10-11.65 (mol of Si)/cm2/s, and ai represents the activity of the subscripted aqueous species.The observation that all rates obtained in the present study can be described by a single regression equation supports strongly the likelihood that basaltic glass dissolution is controlled by a single mechanism at both acidic and basic pH and in both the presence and absence of organic acids. Taking account of the dissolution mechanisms of similarly structured and compositioned minerals, and previously published studies of basaltic glass dissolution behavior, basaltic glass dissolution likely proceeds via 1) the relatively rapid and essentially complete removal of univalent and divalent cations from the near surface; 2) aluminum releasing exchange reactions between three aqueous H+ and Al in the basaltic glass structure; followed by 3) the relatively slow detachment of partially liberated silica. The breaking of Al-O bonds does not destroy the glass framework; it only partially liberates the silica tetrahedral chains by removing adjoining Al atoms. Basaltic glass dissolution rates are proportional to the concentration of partially detached framework Si tetrahedra near the surface, which is linked through the law of mass action for the Al/proton exchange reaction to aqueous aluminum activity.